(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
The article examines the significance of speech culture as an important aspect of professional and personal communication, especially for students of non-linguistic universities. It emphasizes that speech culture includes not only literacy but also the ability to correctly choose words, construct coherent statements, observe speech etiquette, and consider the context of communication. The author reveals the role of speech culture in successful professional interaction, effective learning, and harmonious interpersonal relationships. Special attention is given to methods of developing speech culture: reading, written and oral practice, self-analysis, receiving feedback, and rhetoric training. In conclusion, it is emphasized that the development of speech culture contributes not only to enhancing professional competence but also to the comprehensive development of personality, strengthening trust, and improving the quality of communication in various areas of life.